Management of Edentulous Microstomia Patient: A Case Report and Classification System - Maria S. Abbasi; Naseer Ahmed; Adil Bin Irfan; Samar Al-Saleh; Tariq Abduljabbar; Fahim Vohra (Hindawi Limited, 2022)
Microstomia is an abnormally reduced oral aperture. In the literature, it is not classified by any particular size criteria, rather defined by its effects on function and esthetics. Prosthodontic management of edentulous patients with microstomia is a challenging task. Use of conventional methods for recording an impression and fabricating prosthesis is not effective in such patients. To fabricate well-fitting prosthesis, accuracy of impression recording important anatomic landmarks is essential. Formation of an exacting custom tray and diagnostic cast is critical for final impression accuracy. Provision of a well-fitting prosthesis in microstomia patient will restore esthetics, comfort, and function with oral and systemic patient wellbeing. This paper presents a case report of managing an edentulous microstomia patient with sectional removable prosthesis. Furthermore, it proposes a novel classification system for microstomia patients according to severity of the condition.